Effects of different compounding of formulae on content of gardenoside in Yin Chen Hao decoction - Liang, Guangyi; Cao, Peixue; Chai, Li; Xian, Furong; Li, Xia (Journal of traditional Chinese medicine, 2002)
In order to observe the effects of the ground and intact Zhi Zi (Fructus Gardeniae) and different combinations of the ingredients and refined single Chinese drug granules in Yin Chen Hao Decoction compound prescription on the contents of gardenoside (an effective component of the prescription), the contents of gardenoside were determined with reversed phase high performance liquid chromatography (HPLC), with acetonitrile-water (15:85) as mobile phase, at wave length 238 nm. The results indicated that the gardenoside-decocted-out rates in the decoctions prepared by different combinations of the ingredients with the ground Zhi Zi (Fructus Gardeniae) all were higher significantly than those in the decoction with intact Zhi Zi (Fructus Gardeniae), and generally, different combinations of the ingredients in the decoction had only little effect on the gardenoside-decocted-out rate.